Teaching Campus Program: A Pedagogical Model to Support New Literacy Skills in Elementary Schools - Ismail, Ismail (Maspul Journal of English Studies, 2023)
Literacy is one of the big challenges in developing countries. Indonesia, which has diverse topography and geography, still shows disparities in education equity. In general, rural children in Enrekang District face significant barriers to accessing effective education services. This shows that universally, the dreams of children who cannot access quality education services, such as the weak pedagogical knowledge of teachers and school infrastructure result in low student participation rates. Worse, many of the children did not attend school regularly because they had to work for the family on the farms. On the other hand, the Teaching Campus Program promises to improve the quality of education in Indonesia. The teaching campus program is a program that provides opportunities for students to study outside the classroom for one semester. By becoming a teacher partner to innovate in developing creative and innovative learning strategies and models in the target education unit. The main focus of the teaching 5 campus program is on improving students’ literacy and numeracy skills in targeted schools specifically in the 3T (Frontier, Remote and Disadvantaged) areas. This paper reports on the assessment of literacy learning through a teaching campus program. It can be concluded that the advantages obtained by elementary school level children in rural areas in teaching literacy make a positive contribution to reading ability. However, students need the support of the home environment to become proficient in communicating.